Dinâmica das águas no Sistema Ambiental Urbano na cidade de Itabaiana-SE - Santos, Antony David de Jesus (2024)
The accelerated growth of cities is a condition noted across the globe. Urbanization has sought to occupy any and all available space in the urban perimeter of cities as a result of the significant increase in the number of people living in urban areas, which now account for around 80% of the population. With the significant number of people exercising their interrelationships in space, it is also possible to observe an increasing number of socio-environmental impacts in cities, especially those related to the urban environmental water system such as floods, floods and floods, mainly arising from the way of organization of urban space and its interference in the environmental system in urbanized river basins. In view of this, it was realized that the rapid urban expansion that occurred in Itabaiana-SE in the middle of the 20th century, and which continues until the present moment, brought with it several socio-environmental impacts from a water perspective, which materializes, in particular, through mentioned impacts that are frequently experienced by the population and reported by the local media. Thus, the present research aims to analyze water dynamics in the Urban Environmental System in the city of Itabaiana. As specific objectives, it is intended to configure the evolution of municipal urban space; identify the geoenvironmental constraints and the occurrence of extreme rainfall events in the spatial area under study between 2000 and 2021; characterize the Urban Environmental System (S.A.U.) of Itabaiana. In order to encompass the totality of socio-environmental relations occurring in the study, it was decided to anchor the analysis in the methodological proposal of the General Systems Theory, which will allow an integrated understanding of the genesis of socio-environmental impacts and possible forms of resolution of such misfortunes. The research methodology is supported by the prism of spatiality and temporality, focused on documentary, empirical and bibliographical analysis, which provided data for the development of scientific research within the scope of socio-environmental dynamics in an integrated manner. Therefore, the research followed the following procedural steps: Delimitation of the study area; Readings of scientific productions about local urban evolution and socio-environmental issues; Survey of geoenvironmental data; Field work; Preparation of the Urban Environmental System of Itabaiana. As a conclusion, it was noted that the process of urban expansion occurs in an accelerated manner, driven by the real estate sector operating in the municipality, which, associated with soil sealing, incorrect disposal of solid waste and incorrect dumping of domestic effluents, corroborates the occurrence of impacts socioenvironmental issues focused on water in the city, which materialize in flooding, floods and pollution of urban water bodies.